2000
DOI: 10.1021/jp001751q
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of the Reaction between HS and Cl Radicals

Abstract: The atmospheric reaction between HS and chlorine radicals was studied theoretically, using ab initio methods. We investigated three reaction possibilities:  HSCl formation, and the production of HCl and sulfur, singlet and triplet. The channels that lead to HSCl and to HCl and S(3P) are spontaneous and exothermic at 298.15 K, and the channel for HCl and S(1D) formation is nonspontaneous and endothermic. In a microcanonical kinetics calculation, the rate constant we obtained for HSCl formation was 2.4 × 10-11 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 19 publications
0
17
1
4
Order By: Relevance
“…We note that, in the case of HSCl, we have shown that after strong volcanic eruptions, a condition in which the concentration of hydrogen sulfide becomes significant, it is very likely that HSCl can be formed, as well as under high pressures [6,7].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…We note that, in the case of HSCl, we have shown that after strong volcanic eruptions, a condition in which the concentration of hydrogen sulfide becomes significant, it is very likely that HSCl can be formed, as well as under high pressures [6,7].…”
Section: Introductionmentioning
confidence: 71%
“…Although, to the best of our knowledge, no results have been found in the literature on the HSeCl species, neither experimental nor theoretical, our previous investigations on the HSCl/HClS [5][6][7] system motivated us also to explore the selenium analogue on the singlet potential energy surface 1 [H, Se, Cl]. We note that, in the case of HSCl, we have shown that after strong volcanic eruptions, a condition in which the concentration of hydrogen sulfide becomes significant, it is very likely that HSCl can be formed, as well as under high pressures [6,7].…”
Section: Introductionmentioning
confidence: 88%
“…In regions of strong volcanic eruptions, the possibility that sulfur halides can act also as a halogen reservoir should be examined, and the spectroscopic characterization of SI would offer a means to probe its presence in various gas phase environments. In the case of HSCl [8,9], we have also shown that under these conditions, it is very likely that this species can be formed and play a role in atmospheric chemistry similar to that of its isoelectronic analogue HOCl. Relevant to this context, we also refer the reader to the theoretical work of Roszak et al [13] on the electronic states of IO, to the investigations on emission spectra obtained by high-resolution and laser-induced fluorescent techniques [14][15][16][17], and to the more recent work on the thermochemical properties of halogen oxides by Peterson et al [18].…”
Section: Introductionmentioning
confidence: 69%
“…In the corresponding sulfur series, very little is known experimentally, and for the two heavier diatomics, SBr and SI, results are practically nonexistent, to the best of our knowledge. Theoretically, the two lighter molecules, SF and SCl, were investigated by Yang and Boggs [4,5], and as part of a long-term project on sulfur halogen species being conducted in our group, not only SCl and SBr [6,7] but potential energy surfaces for closely related triatomic and tetratomic systems like HSCl, HClS [8,9], HSSCl, HSClS, HClS 2 [10], and SSX 2 and XSSX, with X = F and Br [11,12] have been extensively investigated with high level ab initio approaches with focus either on spectroscopy or on structure, stability and thermochemistry. In regions of strong volcanic eruptions, the possibility that sulfur halides can act also as a halogen reservoir should be examined, and the spectroscopic characterization of SI would offer a means to probe its presence in various gas phase environments.…”
Section: Introductionmentioning
confidence: 99%
“…It is our hope that the tools here developed should prove reliable enough to investigate in a near future the dynamics not only of the [H, O, I] surface, but also of new triatomic systems such as [H, S, X] (X = Cl, Br, and I), described in previous works in our group. [16][17][18] …”
Section: Introductionmentioning
confidence: 99%